PENDEKATAN PENGELOLAAN KEUANGAN SEKOLAH MENENGAH ATAS DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN - Hadi Siswanto, Deny; Fatimah, Noor (Jurnal Lingkar Mutu Pendidikan, 2024)
This study aims to identify the approach to school financial management that can enhance the quality of education. The method used is qualitative, with the research conducted at Muhammadiyah Mlati Senior High School. Data collection was carried out through observations, interviews, and documentation. Data analysis utilized an interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. To ensure the validity of the data, the researcher conducted triangulation and referred to other references. The results of the study indicate that the financial management of the school in improving the quality of education at Muhammadiyah Mlati Senior High School involves seven stages: (1) holding meetings at the beginning of the academic year; (2) formulating programs; (3) preparing budgets; (4) conducting revision discussions; (5) evaluating outcomes; (6) providing feedback; and (7) preparing the School Revenue and Expenditure Budget Plan (RAPBS).